2022
DOI: 10.1007/s11033-022-08104-7
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor-like 1 (FCRL1) is a novel biomarker for prognosis and a possible therapeutic target in diffuse large B-cell lymphoma

Abstract: BackgroundDiffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin's lymphoma (NHL), which can involve various types of mature B-cells. The incidence of DLBCL has been increased, additional research is required to identify novel and effective prognostic and therapeutic molecules. Fc receptor-like 1 (FCRL1) act as an activation co-receptor of human B-cells. Aberrant expression of this molecule has been reported in a number of B-cell-related disorders. Moreover, the clinical signi cance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Cell cycle analysis by propidium iodide staining showed that frequencies of G2/M cells were reduced, but sub-G1 and G1 cells were increased in hFCRL1-depleted cells after 72 hours, indicating higher levels of apoptosis. Although the rigor of these FCRL1 deficiency studies ( 108 , 109 ), with respect to targeting efficiency and numbers of replicate experiments are somewhat unclear, the results are consistent with observations of positive roles for FCRL1 in B cell proliferation and survival.…”
Section: Fcrl1 Promotes B Cell Activation and Proliferationsupporting
confidence: 74%
See 1 more Smart Citation
“…Cell cycle analysis by propidium iodide staining showed that frequencies of G2/M cells were reduced, but sub-G1 and G1 cells were increased in hFCRL1-depleted cells after 72 hours, indicating higher levels of apoptosis. Although the rigor of these FCRL1 deficiency studies ( 108 , 109 ), with respect to targeting efficiency and numbers of replicate experiments are somewhat unclear, the results are consistent with observations of positive roles for FCRL1 in B cell proliferation and survival.…”
Section: Fcrl1 Promotes B Cell Activation and Proliferationsupporting
confidence: 74%
“…These studies did not assess the impact of BCR stimulation, but 48 hours after FCRL1 knockdown, transcripts encoding the anti-apoptotic gene B cell lymphoma 2 ( BCL2) were lower, whereas the pro-apoptotic BH3 interacting-domain death agonist ( BID) and BCL2-associated X protein ( BAX) genes rose. A follow up report using this shRNA approach in primary DLBCL patient samples indicated similar defects in proliferation and apoptosis ( 109 ). Cell cycle analysis by propidium iodide staining showed that frequencies of G2/M cells were reduced, but sub-G1 and G1 cells were increased in hFCRL1-depleted cells after 72 hours, indicating higher levels of apoptosis.…”
Section: Fcrl1 Promotes B Cell Activation and Proliferationmentioning
confidence: 96%
“…Cheminant et al found that KIR3DL2 is a underlying target of acute adult T‐cell leukemia 45 . Meanwhile, FCRL1 was also reported as a possible prognostic marker for diffuse large B‐cell lymphoma 46 . ZNF541 was discovered to be related to the radiosensitivity of breast cancer 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it is a poor prognostic marker for non-small cell lung cancer (42), but there is currently a lack of research on its relationship with glioma. Fc receptor-like protein (FCRL) is a marker for multiple B-cell tumors (43,44), but its relationship with non-lymphatic system tumors such as glioma is still unclear, which requires further research.…”
Section: Discussionmentioning
confidence: 99%